Typology of preachers in digital da'wah on social media in Indonesia - Nurul Khotimah; Nasihun Amin; Ilyas Supena (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2026)
The phenomenon of Islamic preachers (da’i) emerging on social media reflects the diversity of da’wah styles and approaches, yet studies on the typology of digital preachers remain limited. This study aims to identify and classify the typology of da’i on social media based on da’wah content, media used, and audience segmentation. Using a qualitative descriptive method, this research employs content analysis of selected da’i's accounts across various social media platforms. The findings reveal three typological dimensions: 1) based on content, da’i are classified as textual or contextual; 2) based on media, as conventional or modern-digital; and 3) based on audience, as general or segmented. This study contributes to a deeper understanding of digital da’wah dynamics. It provides a practical framework for researchers and practitioners to develop more relevant and effective da’wah strategies in the social media era.